Transformasi Identitas Keindonesiaan Mahasiswa IAI Tulangbawang dalam Penggunaan Bahasa Inggris sebagai Bahasa Global - Lusi Elisa; Bujang Rahman; Risma Margaretha Sinaga (CV. Creative Tugu Pena, 2024)
This research aims to examine the transformation of IAI Tulangbawang students' Indonesian identity in the context of using English as a global language. In the era of globalization, English has become the main communication tool in the world of education, media and professionals which has the potential to influence students' understanding of their cultural identity. This research uses a qualitative approach with a phenomenological type of research to explore an in-depth understanding of students' experiences, views and perceptions regarding the influence of the use of English on Indonesian identity. This research found that although the use of English provides opportunities to access global information and increase academic competitiveness, there are concerns about losing ties to local culture and Indonesian values. Most students still feel that Indonesian and regional languages ​​are an integral part of their identity, even though they also actively use English in academic and social contexts. This identity transformation is not only influenced by openness to global culture, but also their efforts to maintain local cultural values, such as mutual cooperation, good manners and cultural diversity. The results of this research show that the influence of English in students' lives creates identity ambiguity, but through character education and cultural activities, students can maintain a balance between their Indonesian identity and their involvement in the global world. This research contributes to the understanding of the role of language in the formation of cultural identity and the challenges faced by the younger generation in maintaining their identity amidst globalization.